Managing front line practice in social care - Statham, Daphne (Research highlights in social work ;, 2004)
Written by key figures in the field of social care training and management this much-needed book provides practice guidance for front line managers in social care. Refocusing attention on the management of practice and accountability within services and to service users, the authors provide a variety of perspectives on how front line managers can support practice. Highlighting important aspects of management, such as promoting knowledge-based practice and continuous professional development through lifelong learning, they discuss major issues such as: setting and monitoring new standards and f.